The impact of green and low carbon agricultural production on farmers’ income in minority areas: a case study of Y Town, Zhijin County, Guizhou Province - Liang, Yanju; Pan, Taoyun; Cai, Yu; Yu, Jinna; Choun, Lychhe (Frontiers in Sustainable Food Systems, 2024)
Developing green and low-carbon agriculture is an important and effective way to promote farmers’ income growth. Given the country’s “dual carbon” goal, the study of the impact of green and low-carbon agriculture on the income of farmers in ethnic minority areas is crucial for China to achieve the goals of socialist modernization and common prosperity. Taking Y Town, Zhijin County, Guizhou Province as an example, this paper uses the OLS regression method to empirically study the impact of green and low-carbon agricultural production methods on the income of farmers in ethnic minority mountainous agricultural areas based on the field survey data of 881 farmers. The regression results indicate that there is a positive correlation between green and low-carbon agricultural production and the household income levels of farmers; adopting green and low-carbon agricultural production technologies can effectively promote the growth of farmers’ household income. In addition, education level, health status, and the new rural social pension insurance have all had a significant effect on the income of rural households, however, due to the difficulty in establishing trust relationships, agricultural service outsourcing has reduced the household income level of farmers. As an example, the land transfer behavior in Y Town has no significant effect on increasing farmers’ incomes. Finally, it is recommended to increase fiscal and financial support as well as effectively enhancing farmers’ policy awareness and perception of green and low-carbon agricultural production technologies by improving farmers’ general trust and institutional trust by strengthening farmers’ agricultural education and skills training while cultivating technology-based farming. At the same time, it is necessary to break the geographical restrictions on land transfer scale and achieve moderate-scale land management while promoting the use and adoption of green and low-carbon agricultural production technologies, thereby improving agricultural production efficiency and product quality, and increasing the sustainable growth of farmers’ income. The main contribution of this study is to expand the research scope of green and low-carbon agriculture to ethnic minorities and mountainous agricultural areas.